Marine products for healthcare : functional and bioactive nutraceutical compounds from the ocean - Venugopal, V. [ (Vazhiyil)] , 1942- (Functional foods and nutraceuticals series, 2009)
Discusses the importance of marine products as a source of nutraceuticals, food additives, and other useful ingredients in health protection and product formulation. This book presents the functional properties of various macromolecules available from seafood and other marine resources such as seaweed and coral reef.